Risk factors of Low Back Pain among Nurses Working in Sarawak General Hospital - Chang, Ching Thon; Philumena Kueh Jing, Fenga; Cheah, W.L (Universiti Sains Malaysia, 2016)
Lower back pain (LBP) is a very common musculoskeletal disorder that affects nurses. Previous studies found various physical and psychosocial risk factors of LBP. This study aimed to determine the risk factors of LBP among nurses working at medical and surgical discipline at a general hospital in Sarawak, Malaysia. A cross-sectional study using self-administered, validated questionnaire was conducted. 141 nurses participated in the study. The mean age of the respondents was 29.1 (± 6.43) years with the mean of 5.9 (± 6.04) years of working experience and 16.3% of the respondents had a history of falls. LBP was significantly associated with age, years of working experience (independent t-test) and history of falls (chi-square test). There was no significant association between LBP and other physical and psychosocial risk factors. The 12-month prevalence of LBP was high and nurses need to prevent LBP from the start of career as it was found to have significant association with age and years of working experience.